RUSSIAN SOFT POWER IN CENTRAL ASIA: CONCEPTUALIZATION AND IMPLEMENTATION (Journal of history-rus, 2021)
This work is devoted to conceptualization of «soft power» concept in academic science, studying Russia as a particular case of a hard country with an alternative approach to soft power. The COVID out break provides another strong argument in favor of changing nature of power in international relations in the 21st century. By another words, the coronavirus revealed the main normative nature of the soft power paradigm, which works well enough in theory but is mostly unproven in the real world. Applying the theory of neoclassical realism to explain the logic of employing Russian soft power, this research is aimed to revealing the effectiveness of the Russian strategy in the Central Asian region, as well as the reasons and factors that determine the advantages of Russian soft power in such weak and at the same time authoritarian countries as Central Asian, where leaders, in their turns, show different external orien tation toward integrational process led by Kremlin. Therefore, personal transnational or «Trans imperial» communications serve as the main transmission mechanism of Moscow.Key words: «soft power», «Russian soft power», neoclassical realism, Central Asia.